2002
DOI: 10.1017/s0265021502000959
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic and postoperative analgesic effects of spinal clonidine as an additive to prilocaine in the transurethral resection of urinary bladder tumours

Abstract: The addition of clonidine 75 micrograms to prilocaine 75 mg for subarachnoid anaesthesia increased the duration of sensory and motor block and reduced the need for additional postoperative analgesics by providing excellent analgesia for about 8 h during recovery from transurethral resection of bladder tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Santiveri et al (22) used 75 µg clonidine to prilocaine in patients undergoing transurethral resection of bladder tumours under spinal anaesthesia and reported prolonged sensory and motor blocks along with reduced postoperative analgesic requirement. De Kock et al (9) used spinal anaesthesia by adding varying doses of clonidine (0, 15, 45 or 75 µg) to ropivacaine in arthroscopy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Santiveri et al (22) used 75 µg clonidine to prilocaine in patients undergoing transurethral resection of bladder tumours under spinal anaesthesia and reported prolonged sensory and motor blocks along with reduced postoperative analgesic requirement. De Kock et al (9) used spinal anaesthesia by adding varying doses of clonidine (0, 15, 45 or 75 µg) to ropivacaine in arthroscopy patients.…”
Section: Discussionmentioning
confidence: 99%
“…The area of mechanical hyperalgesia at 72 h was 3±5 cm Some research has shown the usefulness of intrathecal clonidine in urology procedures, although there are some controversies. In a controlled, prospective, double-blind investigation with patients undergoing elective transurethral resection of bladder tumours under spinal anaesthesia [47] the authors found that adding clonidine 75 µg to prilocaine 75 mg increased the duration of sensory and motor block and reduced the need for additional postoperative analgesics by providing excellent analgesia for about 8 hours during recovery period. In a similar study, 25 µg spinal clonidine improved bupivacaine spinal anaesthesia: shorter time to achieve complete motor block and sensory block at T9 level, with longer postoperative analgesia.…”
Section: General Surgery and Urologic Proceduresmentioning
confidence: 99%
“…28 The addition of clonidine 75µg to prilocaine 75mg for subarachnoid anaesthesia reduced the need for additional postoperative analgesics for about 8 hours during recovery from transurethral resection of bladder tumors. 29 The addition of clonidine (15μg and 30μg) to bupivacaine prolonged time to first analgesic request. We have found similar evidence in present study.…”
mentioning
confidence: 99%